Multi-wavelength observations of the flaring gamma-ray blazar 3C 66A IN 2008 october - Abdo, A. A. (2011)
The BL Lacertae object 3C 66A was detected in a flaring state by the Fermi Large Area Telescope (LAT) and VERITAS in 2008 October. In addition to these gamma-ray observations, F-GAMMA, GASP-WEBT, PAIRITEL, MDM, ATOM, Swift, and Chandra provided radio to X-ray coverage. The available light curves show variability and, in particular, correlated flares are observed in the optical and Fermi-LAT gamma-ray band. The resulting spectral energy distribution can be well fitted using standard leptonic models with and without an external radiation field for inverse Compton scattering. It is found, however, that only the model with an external radiation field can accommodate the intra-night variability observed at optical wavelengths.